Development Of Nigerian Federalism And Fiscal Federalism: The Methodological Approaches Of Confusion And Realities. - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Forum of Researchers and Lecturers, 2025)
It is well known that the fiscal federalism pattern that the military imposed on the country disregards the source of money and productivity. This study assessed Nigeria's fiscal federalism. in an effort to pinpoint the trouble spots. The survey research approach was used. The Z-test was used to assess the data gathered from the questionnaire. The results showed that the government-appointed commissions' recommendations on fiscal federalism had little effect on the economy because of a number of issues, including the 1999 constitution's flaws and the numerous issues with fiscal federalism that have resulted in the duplication of government operations and the waste of public funds. Nonetheless, among other things, it is advised that public officials follow the Nigerian fiscal responsibility bill and due process in order to guarantee an effective and sound fiscal federalism in Nigeria. Furthermore, it is important to make sure that all levels of government follow the constitutional provisions on budgetary relations, accountability, and transparency. Establishing a National Fiscal Commission is also advised in order to improve intergovernmental cooperation and understanding in ways that encourage communication between actors in the federal, state, and municipal governments.